Validity of Kirkpatrick Evaluation Model Instrument for Drug Prevention Education Programs in Primary School - Jusoh, Ahmad Jazimin; Abdul Rashid, Nazre; Raja Yusof, Raja Jamilah; Wahab, Suzaily; Abdullah, Azizi; Walid, Durrah Athirah (Universitas Negeri Padang, 2024)
One of the evaluation models generally used in prevention programs is the Kirkpatrick evaluation. The model is used to escort the evaluation program closer to its effectiveness. Kirkpatrick's framework consists of four levels: reaction, learning, behaviour, and result. The purpose of the current research was to assess the validity of the Kirkpatrick evaluation model instrument for drug prevention programs in primary school students in Malaysia. This study used a survey research design by involving 692 primary school students in Malaysia. Three procedures were used to analyse the data in this research, namely Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA) and Cronbach Alpha. EFA revealed the structure of the Kirkpatrick evaluation model which the reaction level has 12 items, the learning level has 8 items, the behaviour level has 6 items, and the result level has 6 items. At the same time, the CFA results showed that the model fit indices established a four-factor structure. Finally, the evaluation model has Cronbach's alpha value of .952, which exceeds the standard (.70 or above). It can be concluded that the Kirkpatrick evaluation model instrument was acceptable and reliable to assess the level of drug prevention programs among primary school students in Malaysia.